2001
DOI: 10.1046/j.1537-2995.2001.41010024.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C antigen in transduced K562 cells

Abstract: The nature of polymorphic residue 226 (proline when E is expressed, alanine when e is expressed) has a marked effect on the epitopes recognized by the three C MoAbs studied. The presence of Cys16 in Ce polypeptides influences the presentation of the C epitope recognized by two of the three MoAbs. These experiments provide the first direct demonstration that C and E/e antigens can be expressed on the same polypeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Our results show that the 48G>C mutation is associated with the RHce allele and is present in both the RHD + as in RHD − haplotypes and, therefore, is not only associated with the R 0 ( cDe ) haplotype, as suggested by Westhoff et al, 21 but is also seen with the r ( cde ) haplotype, especially in black populations (2.4% in Ethiopian donors and 22.4% in Curaçao donors). Although C16 is involved in C expression, 6 clearly other conformation‐determining factors are also required for the expression of C. However, it is highly unlikely that this variant RHce is immunogenic for transfusion recipients and/or mothers lacking this gene. Serologic analysis with MoAbs directed against each of the five different c epitopes as described by Faas et al 5 showed that the 48G>C mutation does not interfere with the expression of any of the c epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that the 48G>C mutation is associated with the RHce allele and is present in both the RHD + as in RHD − haplotypes and, therefore, is not only associated with the R 0 ( cDe ) haplotype, as suggested by Westhoff et al, 21 but is also seen with the r ( cde ) haplotype, especially in black populations (2.4% in Ethiopian donors and 22.4% in Curaçao donors). Although C16 is involved in C expression, 6 clearly other conformation‐determining factors are also required for the expression of C. However, it is highly unlikely that this variant RHce is immunogenic for transfusion recipients and/or mothers lacking this gene. Serologic analysis with MoAbs directed against each of the five different c epitopes as described by Faas et al 5 showed that the 48G>C mutation does not interfere with the expression of any of the c epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Although S103 is critical, C antigenicity has to be determined by other amino acids as well, as S103 is also present in the D polypeptide. K562 transfection studies clearly showed the importance of C16 in C expression 6 . It has been suggested that the interaction with the third extracellular loop is probably also required for some C epitopes.…”
mentioning
confidence: 97%
“…For full expression of C, the protein must have Ser103, Cys16, and some other downstream amino acids characteristic of the RhCE protein. The C/c polymorphism, however, has no obvious effect on the expression of E [311] . RHD -CE -D s produces weak partial C [129 -131,312] .…”
Section: The C/c Polymorphismmentioning
confidence: 88%
“…C, therefore, is a very conformational antigen and anti -C are heterogeneous. Pro226, therefore, appears to suppress C expression [311] . Cys16 is not a requirement for all epitopes of C. RHD -CE -D s , part of the d(C)ce s haplotype that is relatively common in Africans, has exons 1, 2, and the 5 ′ end of exon 3 derived from RHD , and so encodes Trp16 and Ser103 from RHD , but Thr152 and the amino acids of the third extracellular loop from RHCE [130] .…”
Section: The C/c Polymorphismmentioning
confidence: 92%
See 1 more Smart Citation